2012
DOI: 10.1016/j.jvs.2011.11.103
|View full text |Cite
|
Sign up to set email alerts
|

First results of clampless distal anastomosis in peripheral vascular bypass with LeGoo, a thermoreversible polymer

Abstract: LeGoo gel can be used to stop blood flow in small-bore arteries in the lower limbs to allow anastomoses to be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…A similar adverse event has been reported previously as part of the learning curve of using this product. 12 Intraluminal flushing of cold saline into the polymer in order to dissolve the plug is of particular importance in calcified vessels, due to the poor thermoconductivity of porcelain arteries. In the rare case when the polymer does not provide adequate haemostasis for suturing, conversion to standard vascular surgical techniques with vessel control using loops or clamps can be easily performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar adverse event has been reported previously as part of the learning curve of using this product. 12 Intraluminal flushing of cold saline into the polymer in order to dissolve the plug is of particular importance in calcified vessels, due to the poor thermoconductivity of porcelain arteries. In the rare case when the polymer does not provide adequate haemostasis for suturing, conversion to standard vascular surgical techniques with vessel control using loops or clamps can be easily performed.…”
Section: Discussionmentioning
confidence: 99%
“…10 The applicability of this technique in peripheral vascular surgery has been shown in initial reports. 11,12 However, the use of this polymer in distal bypasses for limbthreatening ischaemia has not been assessed yet.…”
mentioning
confidence: 99%
“…Surrounding tissues should be sufficiently retracted with sufficient exposure, and bleeding should be minimized. [10,11] The traumatic effects of surgical procedures and devices that provide bloodless intervention have been known for decades. [12] Most vascular injury studies have focused on vascular clamps because of the common use of such devices.…”
Section: Tukey Hsdmentioning
confidence: 99%
“…[11] Despite the advanced techniques, vascular clamps are still the most highly available devices to stop bleeding and provide good operation conditions. [10,11] Manship et al [13] demonstrated vascular endothelial and presumed medial injury in clamped vessels using all types of vascular clamps, and they claimed that vascular loops could protect the vascular endothelium better. Thereafter, Margovsky et al [2] described a measurement of an endothelial injury method by staining an endothelial surface area, and reported that vascular clamps lead to increased endothelial injury.…”
Section: Tukey Hsdmentioning
confidence: 99%
“…In peripheral vascular surgery, it has achieved a satisfactory bloodless field in 92% of anastomoses 4 and a mean occlusion time of 13.4 minutes. 5 We present this combined open surgical and endovascular technique that used poloxamer 407 as a temporary occlusion device during the surgical resection of a CBT.…”
mentioning
confidence: 99%